Mortgage Loan Flow Networks and Financial Norms - Stanton, Richard; Walden, Johan; Wallace, Nancy (Review of Financial Studies, 2018)
We develop a theoretical model of a network of intermediaries whose optimal behavior is jointly determined, leading to heterogeneous financial norms and systemic vulnerabilities. We apply the model to the network of U.S. mortgage intermediaries from 2005 to 2007, using a data set containing all private-label, fixed-rate mortgages, with loan flows defining links. Default risk was closely related to network position, evolving predictably among linked nodes, and loan quality estimated from the model was related to independent quality measures, altogether pointing to the vital importance of network effects in this market. Received April 20, 2016; editorial decision July 11, 2017 by Editor Stijn Van Nieuwerburgh.